Detention of Child Asylum Seekers in the Pursuit of State Interests: A Comparison of the Australian and EU Approaches. Issue 1 (2nd January 2018) - Del Gaudio, Eleonora; Phillips, Stephen
ABSTRACT: The widespread use of detention of asylum seekers as a form of controlling borders and migration is an acknowledged reality that carries a particular significance in cases where children are involved. Many studies provide evidence on the detrimental impact of detention, especially when this measure affects particularly vulnerable persons. This article is an inquiry into the detention of child asylum seekers in Australia and the European Union (EU). The right to liberty in the asylum context and the protection needs of children are addressed from a legal and policy perspective. The two examined situations display significant differences, yet many commonalities can also be traced in the increasingly restrictive approach to migration favoured by many states. This paper builds on existing arguments and evidence by demonstrating how detention of asylum seeking children has become a matter of policy rather than a measure of last resort, with children not seen first as children, but as detainable foreign subjects. Hence, this analysis questions the logic behind the capacity of states to detain children due to their migration status and identifies relevant protection gaps within the Australian and EU spheres.